(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
This research aims to detect and analyze the change in vegetation cover density in the city of Tripoli and its suburbs during the period (2016–2025) using remote sensing and (GIS). Sentinel-2 satellite images, which were freely downloaded from the European Union’s Copernicus Browser website, were used, and the data was processed and analyzed with ArcGIS Pro software. The study adopted the use of the Atmospherically Resistant Vegetation Index (ARVI) with a Normalized Difference Vegetation Index (NDVI) mask, using bands B3, G8, and R7, and the Ocean and Land Colour Imager (OLCI). This methodology integrated the ARVI index with a mask based on the NDVI, which assigned zero values to bare lands while preserving positive values to represent vegetation at various densities. This processing yielded more accurate results in isolating non-vegetated areas while maintaining ARVI’s key feature of resistance to atmospheric effects. The study revealed a significant deterioration of vegetation cover in Greater Tripoli during the study period, based on the ARVI index data. The level of bare land occupied the largest area among all land cover types, with a percentage of 91% in 2017, 92% in 2018, 2019, and 2022, 93% in 2016 and 2025, 94% in 2021, 2023, and 2024, and 95% in 2020, Therefore, the study recommended that institutions concerned with preserving vegetation cover in Libya must integrate and communicate to exchange expertise and research projects to achieve sustainable environmental protection for vegetation and combat climate change.